Analisis Keterlibatan Konsumen Terhadap Kesediaan Membayar Harga Premium Pada Produk Fashion, Dimediasi oleh Status Merek dan Sikap Konsumen Terhadap Merek - Dani Rizqi Rakhman; Budi Astuti (Forum Manajemen Indonesia (FMI), 2015)
Adolescents are very attention to their physical appearance, with regard to physical appearance, adolescents make efforts so that their physical appearance in accordance with the guidance of their social community. One product supporting physical appearance often hunted adolescents clothing. Based on this phenomenon, the researchers interested in studying about the analysis of consumer involvement toward willingness to pay a premium on fashion products, mediation by brand status and brand attitude. The purpose of this study was to determine the effect of consumer involvement on brand status of fashion products and brend attitude, then the influence of the brand status of fashion products and brand attitude toward the willingness to pay a premium price. This study used questionnaires distributed to adolescents aged 18-21 years, then the data is processed using an analysis SEM (Structural Equation Model) via AMOS software. Results from this research that consumer involvement has a positive and significant effect on the brand status and brand attitude, then the brand status of fashion products and brand attitude have a positive and significant impact on the willingness to pay a premium price. Key Words : Consumer Involvement, Brand Status, Brand Attitude, Willingness To A Pay Premium.